Histopathological study of upper versus lower poles of tonsil in chronic tonsillitis among pediatric age group - M. S., Sudhakar Rao; P., Apoorva; K. M., Bindu Rani; G., Shadakshari (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: To compare the histopathological findings between upper and lower poles of tonsil in pediatric age group keeping in view the local and distant effects of chronic tonsillitis. Methods: Three relevant parameters, grade of inflammation (GOI), activity of inflammation and hyperplasia were histopathologically examined in the tonsils of n=60 pediatric patients with chronic tonsillitis who underwent tonsillectomy in Department of Otorhinolaryngology and Head and Neck Surgery, VIMS, Ballari, Karnataka, India. These parameters were analyzed and were subjected for statistical analysis. Results: In our study, among 60 patients, n=32 (54.2%) were female and n=28 (45.8%) were male. Those aging 5-10 years were n=34 (57.6%) and 11-15 years were n=26 (42.4%). The tonsillar enlargement of grade 3 were present in n=46 patients (77.7%), n= 12 patients (20%) had grade 2 and n=2 patients (1.3%) had grade 4. Conclusions: The GOI and hyperplasia parameters in our study have highly significant association statistically (p<0.01) in histopathology of upper poles when compared with lower poles both sides. Further, the activity of inflammation when analyzed was more in upper pole when compared with lower poles both sides, However this parameter in left side upper and lower poles of tonsil was not statistically significant . Among the 60 cases studied, in all the cases, the GOI was of high grade and activity of inflammation and hyperplasia was low grade. Chronic tonsillitis and histopathology of chronically infected tonsils becomes an important step in the management of the disease.